Can input access and market-based incentives reduce food loss? The case of bean farmers in Guatemala and Honduras - Delgado, Luciana; Nakasone, Eduardo; Torero, Máximo (International Food Policy Research Institute, 2021)
Rapid population growth, urbanization, and increasing pressure on the world’s available agricultural land all pose challenges to food security. Policies to address them aim to increase agricultural yields and productivity rather than reducing food loss. Research on food loss reduction and its impact on improving food security has been limited, with much of the focus on technical interventions to reduce losses at post-harvest stages. Specifically, studies focus on storage and offer limited evidence on where losses occur in the value chain and how cost-effective the interventions are (Stathers et al., 2020). Building on Delgado et al. (2021 a, b) and FAO (2019), whose findings identified that food loss is not only significant at post-harvest stages but also at the pre-harvest level; this paper tested a market-based incentive intervention that could reduce food loss across the value chain. The intervention provided farmers with information on the attributes of food quality buyers required to pay a market price premium. If those attributes were achieved, then it meant that the intervention could lead to food loss reduction, outperforming traditional reduction policies set out by governments, including the provision of input packages. To test this market-based incentives, a randomized control trial (RCT) was conducted with bean producers in Guatemala and Honduras. The results showed that farmers who received market-oriented incentives had reduced bean losses by 6 percent in Guatemala and by 7 percent in Honduras compared with the control group. The results suggested that it could be more effective for governments to switch policies from simply providing input packages to promoting market-based incentives, and share information on standards and promote standards legislation and price premiums at wholesale markets and for agro-processors.